Evolving Character of Chronic Central Nervous System HIV Infection - Price, Richard W. (2014)
Human immunodeficiency virus type 1 (HIV-1) infection of the central nervous system (CNS) begins early in systemic infection and continues throughout its untreated course. Despite a common cerebrospinal fluid inflammatory response, it is usually neurologically asymptomatic for much of this course, but can evolve in some individuals to HIV-associated dementia (HAD), a severe encephalopathy with characteristic cognitive and motor dysfunction. While widespread use of combination antiretroviral therapy (ART) has led to a marked decline in both the CNS infection and its neurologic severe consequence, HAD continues to afflict individuals presenting with advanced systemic infection in the developed world and a larger number in resource-poor settings where ART is more restricted. Additionally, milder CNS injury and dysfunction have broader prevalence, including in those treated with ART. Here we review the history and evolving nomenclature of HAD, its viral pathogenesis, clinical presentation and diagnosis, and treatment.